Estudo comparativo entre métodos de coloração para a pesquisa do bacilo álcool-ácido resistente em secreções pulmonares A comparative study between two staining methods employed in the search of alcohol acid resistant bacilli in pulmonary secretions - Clara Pechmann Mendonça; Vera Lygia Ferreira Lourenço; Mario Tsunezi Shimizu; Paulo Roberto Natalino; Ivone Shizuko Anno; Romanoff Jorge S. Haddad; José Dario Prada; Geraldo Campos Costa (Universidade de São Paulo, 1975)
Apresentação do resultado comparativo entre dois métodos de coloração Osol e Ziehl-Neelsen para a pesquisa do bacilo álcool-ácido resistente, em 337 amostras secreção pulmonar. Foi realizada uma avaliação cultural de 287 amostras, mostrando que o método de Osol apresenta-se melhor nas baciloscopias discordantes e que há tendência em apresentar maior riqueza de germe. The comparative results obtained with the study of two staining methods, the Ziehl-Neelsen and the Osol ones, are presented. The study was performed with the alcohol acid resistant bacilli of 337 pulmonary secretion specimens. Evaluation cultures of 287 of these specimens were made. The Osol method proved to be better than the Ziehl-Neelsen one when dealing with discordant baciloscopic evidence. There tended to be a larger ammount of bacilli, too, when the former was used.